Community structure of superfamily trochoidea (Mollusca Gastropoda) in coral reef sites in Taklong Island National Marine Reserve, Guimaras. - Cagampang, Ma. Thrysky Kharmylle A.
Mollusks are considered to be one of the most diverse animal groups. These are widely distributed in tropical areas such as Philippines. One of the most diverse classes of Phylum Mollusca is Class Gastropoda. It is comprised of more than 65,000 species. Superfamily Trochoidea is considered to be its largest superfamily with more than 2000 species. Guimaras is a province here in the Philippines. There are a variety of islands that can be found in Guimaras. One of this is Taklong Island located in the municipality of Nueva Valencia. This study describes the community structure of Superfamily Trochoidea in three selected reef flat sampling sites namely, Talisay Kalirohan, and Banago in Taklong Island National Marine Reserve (TINMR). Plot method was used in this study. There was a total of 369 gastropod individuals collected but only 242 were alive. Live samples belonged to 12 families including 2 families of Super Family Trochoidea, namely, Trochidae and Turbinidae. There were 8 species identified that belonged to these 2 families of Superfamily Trochidea. Under family Trochidae, was 1 species, Tectus fenestratus; under family Turbinidae were three species, namely, Astralium calcar, Astralium provisorium and Turbo argyrostomus. Dead species of Family Trochidae include Trochus conus, Trochus hanleyanus, Trochus sp. and Trochus maculates. In general, Astralium calcar was found to be the most abundant among live species. The low diversity of trochoids reported in this study could be an underestimate due to sampling design. Most species of Superfamily Trochoidea, especially the topshells, are nocturnal while this study was conducted at daytime. In general, the gastropod community in TINMR proved to be rich and diverse.